2018
DOI: 10.1177/0033294118771705
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Emotional Intelligence After an Online Training Program Are Associated With Better Decision-Making on the Iowa Gambling Task

Abstract: Higher levels of emotional intelligence have been associated with better inter and intrapersonal functioning. In the present study, 59 healthy men and women were randomized into either a three-week online training program targeted to improve emotional intelligence ( n = 29), or a placebo control training program targeted to improve awareness of nonemotional aspects of the environment ( n = 30). Compared to placebo, participants in the emotional intelligence training group showed increased performance on the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 56 publications
2
38
0
1
Order By: Relevance
“…These findings also suggest that individuals with higher levels of TEI make decisions with higher quality in comparison to individuals with lower TEI levels. This coincides with previous data reporting a facilitative effect of TEI on decision-making (Alkozei et al, 2016;Alkozei et al, 2018;Fallon et al, 2014;Pilarik & Sarmany-Schuller, 2009). Moreover, athletes with higher TEI may be more proficient at regulating emotion and achieving optimal mood states associated with improved performance (Lane et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings also suggest that individuals with higher levels of TEI make decisions with higher quality in comparison to individuals with lower TEI levels. This coincides with previous data reporting a facilitative effect of TEI on decision-making (Alkozei et al, 2016;Alkozei et al, 2018;Fallon et al, 2014;Pilarik & Sarmany-Schuller, 2009). Moreover, athletes with higher TEI may be more proficient at regulating emotion and achieving optimal mood states associated with improved performance (Lane et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The findings indicated a positive relationship between athletic expertise and TEI with quality of decisions, and a negative relationship of athletic expertise and TEI with risk-taking and deliberation time. The findings largely corroborate previous research indicating a facilitative link between athletic expertise and TEI with decision-making ability (e.g., higher quality, less risk and deliberation), on a non-specific decision-making task (Alkozei et al, 2016;Alkozei et al, 2018;Fallon et al, 2014;Panno, 2016;Pilarik & Sarmany-Schuller, 2009). The significant relationship between TEI and decision-making demonstrated a combined effectiveness that may be tapped during athletic performance.…”
Section: Discussionsupporting
confidence: 88%
“…For example, Buelow and Blaine (2015) analyzed undergraduate performance on the IGT, balloon analogue risk task, and Columbia card task and concluded that these tasks measured unique, nonoverlapping decision-making processes. Alkozei and colleagues found that participants performed better on the IGT after an emotional intelligence training program (Alkozei et al, 2018). Simonovich, Stupple, Gale, and Sheffield (2018) discovered that stress reduced performance on the IGT, but reflective thinking and conscious awareness mediated this effect (Simonovich et al, 2018).…”
Section: Studymentioning
confidence: 99%
“…The quality of decision in this regard contributes to the risk attitude assumed in the face of uncertainty. While EI can improve decision quality, as shown by Alkozei et al (2019) and Fallon et al (2014), there is scope to model the flow of decision and the emotional regulation of decision-making process from the incipient presentation of facts, their passage through the personal subjective mental lens of the decision maker, and, appropriation or assumption of an informed risk attitude leading to the final decision.…”
Section: Theoretical and Literature Reviewmentioning
confidence: 99%